MAKNA POLA LANTAI TARI NYIGAL DALAM UPACARA GAWIA DI DUSUN JAGOI KINDAU KABUPATEN BENGKAYANG - Nova, Erni; Fretisari, Imma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research was to describe floor patterns of Nyingal, describe the meaning of floor patterns of Nyingal dance, and the lesson plans. Due to this importance, descriptive method in form of qualitative through ethnography approach was necessary. The sources of data used were two interviewees with the technique of triangulation and lengthened observation. Gawia ritual was a ceremony held after rice-harvest. In the ritual of Gawia, there was a dance which the floor pattern has meaning. The floor pattern which had meaning in the ritual of Gawia namely, horse shoe floor pattern â€œUâ€, straight floor pattern, and round floor pattern. The meaning mentioned in horse shoe floor pattern â€œUâ€ was that the soul of ancestors alive during the Gawia ceremony, the meaning which straight floor pattern brings was respecting to Topa (The God) and the soul of ancestors and the last was the meaning of straight floor pattern, namely asking for grace. The result of this research was expected to be implemented in a lesson plan in grade VIII on the floor pattern of Nyingal dance in Art and Culture subject.Â Keywords: Meaning, Floor Pattern, Nyingal DanceÂ